Enhancing isolation performance of tilted Beam MIMO antenna for short-range millimeter wave applications - Wahaj Abbas Awan; Esraa Mousa Ali; Mohammed S. Alzaidi; Dalia H. Elkamchouchi; Fahad N. Alsunaydih; Fahd Alsaleem; Khaled Alhassoon (Heliyon, 2023)
The research paper discusses the detailed designing of a compact, simple, and low-profile antenna that provides several desirable features. The antenna is engineered by using a substrate material called Roger 6002, and its dimensions are 12 mm × 6 mm × 1.52 mm. The single antenna element achieves a wideband frequency coverage of 24–30.2 GHz and a high gain of 9 dBi. To enhance the antenna's capabilities, a two-port multiple-input multiple-output (MIMO) configuration is employed by adding a second antenna element orthogonal to the first one. Although the operational band remains the same, the isolation between the two elements is found to be unsatisfactory. A C-shaped decoupling structure is established to address this issue, which effectively improves the isolation. Including the parasitic patch enhances the isolation from −18 dB to −29 dB. An antenna hardware sample is built and tested to validate the recommended work, and the outcomes are compared to the predicted results obtained from the software. The experimental and simulated data exhibit close agreement, confirming the accuracy of the design. Additionally, this outstanding performance in bandwidth and isolation compares with existing literature, presented in the form of a table. Various MIMO parameters are also examined, and it is found that they fall within acceptable ranges. The antenna demonstrates an Envelope Correlation Coefficient (ECC) of approximately 0.005 and a Diversity Gain (DG) of around 9.99 dB. The recommended antenna design is highly suitable for future miniature devices used in Internet of Things (IoT) applications.